Succession dynamics of the sierra de Alvarez oak forests in San Luis Potosí, México - Castillo Lara, Pedro; Flores Cano, Jorge Alberto; Aguirre Rivera, Juan Rogelio; Yeaton H., Richard I. (Instituto de Ecología, A.C., 2016)
The effect of interspecific competition on the dynamics of temperate forests in Mexico has rarely been investigated. In this study, the dynamics of an oak forest in the Sierra Madre Oriental are described using techniques involving strong inference. In particular, methods are presented to determine which species are important in the tree community, the sequence of establishment of these species, the competitive replacement of one species by another and, finally, how each species’biology affects their succesional status. The results show a sequence of three species of red oaks (Quercus coccolobifolia, Q. cras sifolia and Q. affinis) replacing one another over time with a fourth species, a white oak Q. obtusata, f u n ctioning as a subdominant to Q. affinis in the late succesional stage of the forest.